Crusoe and his consequences - Dunkerley, James (OR Books, 2019)
300 years after it was first published, Daniel Defoe's Robinson Crusoe remains hugely influential and hotly debated. Since its initial release in 1719, discussions have surrounded the novel's depiction of individual solitude and work, colonial and racial relations, and mankind's relationship with the rest of the animal world. To this day, Crusoe's depiction of self-reliance and "rugged individualism" is often idealized in economics textbooks, mainstream politics, and popular culture. But many have also criticized this approach, most notably Karl Marx, who was one of the first in decrying the efforts of classical economists to extract the "rational actor" and "marginalist calculator" from the island castaway without reference to social history. Alongside a precis with surprising revelations for those not familiar with the detail of the story, and a rich biographical sketch of its creator, Crusoe and His Consequences draws on a range of writers, including Adam Smith, Jean-Jacques Rousseau, Jacques Derrida and Jurgen Habermas, to bring the debates surrounding Defoe's first novel vividly to life. --